2015 IEEE 7th International Conference on Cybernetics and Intelligent Systems (CIS) and IEEE Conference on Robotics, Automation 2015
DOI: 10.1109/iccis.2015.7274617
|View full text |Cite
|
Sign up to set email alerts
|

Modular relative Jacobian for dual-arms and the wrench transformation matrix

Abstract: Abstract-A modular relative Jacobian is recently derived and is expressed in terms of the individual Jacobians of stand-alone manipulators. It includes a wrench transformation matrix, which was not shown in earlier expressions. This paper is an experimental extension of that recent work, which showed that at higher angular end-effector velocities the contribution of the wrench transformation matrix cannot be ignored. In this work, we investigate the dual-arm force control performance, without necessarily drivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Different ways to derive the relative Jacobian has been illustrated in [5], [12] and [17]. The present work applies the procedure presented in [12].…”
Section: B Relative Jacobian and Manipulabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Different ways to derive the relative Jacobian has been illustrated in [5], [12] and [17]. The present work applies the procedure presented in [12].…”
Section: B Relative Jacobian and Manipulabilitymentioning
confidence: 99%
“…As shown in Section II-B, this allows the reduction of the dual-arm system to a single-armlike manipulator. In this way, the manipulability ellipsoids may be directly derived from the so-called relative Jacobian (see [12]). This strategy has been applied, for instance, in [2] and [13].…”
Section: Introductionmentioning
confidence: 99%
“…relative Jacobian of dual-arm robots A and B 4 to those frames. From the figure, we state the following conventions for the Jacobians of the standalone manipulators.…”
Section: Naming Convention For Symbolsmentioning
confidence: 99%
“…In a new derivation of a modular relative Jacobian for dualarms [3], a wrench transformation matrix was revealed that was not present or was not explicitly expressed in the previous relative Jacobians. Further studies shown in [4] highlighted the effects of the omission of the wrench transformation matrix on the exerted forces and moments at the dual-arm end-effectors, such that at certain configurations, its omission lead to non-contact for task that requires contact all the time. Asymmetric bimanual task was shown [5] for dual-arm performing at writing task using a relative Jacobian.…”
Section: Introductionmentioning
confidence: 99%
“…A more compact modular relative Jacobian was first shown n [10], which reveals a wrench transformation matrix that was not present or was not explicitly expressed in the previous relative Jacobians. It was further shown that omission of the wrench transformation matrix can affect the performance of the dual-arm, including the forces and moments exerted at the endeffectors [11]. The concept of a relative Jacobian was [13].…”
Section: Introductionmentioning
confidence: 99%